Reversible cardiac dysfunction in severe COVID‐19 infection, mechanisms and case report. Issue 9 (27th August 2020) - Chao, Chieh‐Ju; DeValeria, Patrick A.; Sen, Ayan; Lee, Hong; Pedrotty, Dawn M; Patel, Bhavesh; Arsanjani, Reza; Naqvi, Tasneem Z.
Abstract: A previously healthy 49‐year‐old male patient presented with COVID‐19 infection and required mechanical ventilation and extracorporeal membrane oxygenation due to severe hypoxemia. Echocardiography showed cardiac dysfunction with an apical sparing strain pattern, which rapidly normalized within a week. Apical sparing myocardial strain in patients with COVID‐19 infection may suggest reverse‐type stress cardiomyopathy.